Physiological Tolerance Mechanism of selected Rice Germplasm of Northeast India to Iron Toxicity - Devi, A. G.; Rangappa, K.; Yadav, G. S.; Devi, H. L.; Barman, K. K.; Kandpal, B. K.; Ngachan, S. V. (Indian Journal of Hill Farming, 2018)
Rice cultivation in lowland faces the iron toxicity stress due to the accumulation of excess ferrous iron in reduced soil condition, and causes reduction in productivity. Therefore, the present study was undertaken to investigate the strategies used by the rice cultivars from North-East region of India under iron excess condition for further improvement of rice through breeding programme. The investigation was carried out in five rice cultivars from North-East India viz. KD-2-6-3, Phougak, Pyzum, Shahsarang, Guwahati and a popular rice hybrid Arize 6444 produced by Bayer Company. Hydroponically grown rice seedlings of the cultivars were exposed to a high Fe concentration (1000 mg L-1 = 17.9 mM Fe2+) and harvested after five weeks to examine the variation in symptom expression in the leaves, biomass retention, tissue iron distribution, root oxidising power and lipid peroxidation. Lowest leaf symptom expression was recorded KD-2-6-3, Guwahati and Shahsarang. Conversely, the symptom expression was severe in case of Pyzum and Phougak. KD-2-6-3 and Arize 6444 recorded the lowest and highest iron concentration in shoot and root tissue, respectively. Lipid peroxidation value was lowest in KD-2-6-3, Guwahati and Shahsarang. The rhizosphere oxidation proceeded at much faster pace in KD-2-6-3 and Arize 6444 than Guwahati and Shahsarang. The root oxidation, though, could not be detected in Pyzum and Phougak. Findings of the study corroborate the differential response to iron toxicity of the rice cultivars with the tolerant rice cultivars employing different tolerance strategies either with shoots- and/or root- based mechanisms.